Strategi Peningkatan Penghimpunan Wakaf Melalui Kegiatan Dakwah di Pesantren Baitul Hidayah - Hendi Suhendi; M. Fauzi Arif; N Sausan M. Sholeh (Universitas Islam Bandung, 2021)
ABSTRACT This study examines strategies to increase the collection of waqf through Islamic Da'wah activities. This is important to do, considering the Baitul Hidayah Islamic Boarding School has a large potential for waqf while the ongoing collection of waqf has not yet reached the expected target. This study aims to find a solution in the form of a strategy to increase the collection of waqf by utilizing da'wah activities as a way of socialization and promotion. This type of research is a qualitative descriptive study, while the data sources are obtained directly in the field (field research). The research approach uses case studies with data collection techniques through interviews, documentation studies and field observations. The results of this study recommend strategies for increasing the collection of waqf through: (i) Optimizing the role of dai as a marketing of waqf. (ii) fulltime managing human resources. (iii) Improvement of Facilities and Infrastructure. (iv) Creating a creative collection program. (v) Standardization of Data Management. (vi) Improvement of convenience services and activity reports.Keywords: Collection, Waqf, Da'wah and Islamic boarding schools. ABSTRAKPenelitian ini mengkaji tentang strategi peningkatan penghimpunan wakaf melalui kegiatan Dakwah Islam. Hal ini penting dilakukan, mengingat Pesantren Baitul Hidayah memiliki potensi wakaf yang cukup besar sementara penghimpunan wakaf yang berjalan belum mencapai target yang diharapkan. Penelitian ini bertujuan untuk mendapatkan solusi berupa strategi peningkatan penghimpunan wakaf dengan memanfaatkan kegiatan-kegiatan dakwah sebagai jalan sosialisasi dan promosi. Jenis penelitian ini adalah penelitian deskriptif kualitatif, adapun sumber data diperoleh langsung di lapangan (field research). Pendekatan penelitian menggunakan studi kasus dengan teknik pengumpulan data melalui wawancara, studi dokumentasi dan observasi lapangan. Hasil penelitian merekomendasikan strategi peningkatan penghimpunan wakaf melalui : (i) Optimalisasi peran dai sebagai marketing wakaf. (ii) SDM pengelola fulltime. (iii) Peningkatan Sarana dan Prasarana. (iv) Menciptakan Program penghimpunan yang kreatif. (v) Standarisasi Pengelolaan Data. (vi) Peningkatan layanan kemudahan dan laporan kegiatan.Kata Kunci: Penghimpunan, Wakaf, Dakwah dan Pesantren.